MICROPLASTICS: A REVIEW ON ITS INFLUENCE ON MARINE SPECIES AND VARIOUS METHODS OF ITS TREATMENTS - DAS, BHABANA; PHUKAN, SOUBHIK; DAS, JYOTISMITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The presence of microplastics in the aquatic system is a major concern of today’s society. Microplastic pollution has caused degradation of the aquatic system and its species. The influence of microplastics on marine species was seen to be significant as microplastics are easily ingested by fishes and other inhabitants of the water bodies due to the small size of microplastics. This review discussed the potential technologies for controlling and recycling of plastics, treatment of municipal waste water, drinking water and marine water bodies through clean up boats, sea bins and trash racks. The current technologies for eliminating microplastics from the environment: 1) Catalytic degradation of microplastics; 2) Agglomeration- fixation using organosilanes; 3) Experimentation with hybrid silica gels are also reviewed here. The objective is to learn and understand the degrading influence of MPs on aquatic habitants so that they adapt, develop and practice the necessary implementations to eliminate microplastics from the water bodies.